Barriers and facilitators to self-monitoring of blood glucose in people with type 2 diabetes using insulin: a qualitative study - Ong, W.M.; Chua, S.S.; Ng, C.J. (2014)
Background: Self-monitoring of blood glucose (SMBG) helps to improve glycemic control and empowerment of people with diabetes. It is particularly useful for people with diabetes who are using insulin as it facilitates insulin titration and detection of hypoglycemia. Despite this, the uptake of SMBG remains low in many countries, including Malaysia. Purpose: This study aimed to explore the barriers and facilitators to SMBG, in people with type 2 diabetes using insulin. Patients and methods: Qualitative methodology was employed to explore participants' experience with SMBG. Semistructured, individual in-depth interviews were conducted on people with type 2 diabetes using insulin who had practiced SMBG, in the primary care clinic of a teaching hospital in Malaysia. Participants were purposively sampled from different age groups, ethnicity, education level, and level of glycemic control (as reflected by the glycated hemoglobin HbA(1c)), to achieve maximum variation in sampling. All interviews were conducted using a topic guide and were audio-recorded, transcribed verbatim, checked, and analyzed using a thematic approach. Results: A total of 15 participants were interviewed, and thematic saturation was reached. The factors that influenced SMBG were mainly related to cost, participants' emotion, and the SMBG process. The barriers identified included: frustration related to high blood glucose reading; perception that SMBG was only for insulin titration; stigma; fear of needles and pain; cost of test strips and needles; inconvenience; unconducive workplace; and lack of motivation, knowledge, and self-efficacy. The facilitators were: experiencing hypoglycemic symptoms; desire to see the effects of dietary changes; desire to please the physician; and family motivation. Conclusion: Participants' perceptions of the purpose of SMBG, the emotions associated with SMBG, and the complexity, pain, and cost related to SMBG as well as personal and family motivation are the key factors that health care providers must consider when advising people with diabetes on SMBG.